An Assessment of Road Landscape by Analysing People’s Perception and Expert Opinion of Khulna City, Bangladesh - Paul, Sneha; Roy, Tusar Kanti (Journal of Engineering Science, 2020)
Road landscape management is essential for a sustainable environment. This study is conducted to show the existing road landscape condition of Khulna city. Both qualitative and quantitative analyses have been done to analyze the existing condition of the road landscape. Urban Landscape Quality Index (ULQI) and Analytical Hierarchy Process (AHP) are used for qualitative and quantitative analysis respectively. In ULQI, the expert's opinion has been compared with the people's perception and 70.6% of similarity is found. From AHP analysis, KDA Avenue is ranked first which indicates that this road possesses the best road landscape and Sher-E-Bangla road is ranked last. The study finds that the road landscape of Khulna city is not in very good condition. For improving the livability and sustainability of Khulna city, investigation of the road landscape both from quantitative and qualitative perspective may establish the basis for future analysis. Journal of Engineering Science 11(2), 2020, 75-86